Shari'ah compliant contract: concept and application for construction works - Abdul Rashid, Khairuddin (2008)
This paper discusses the concept and application of Shari'ah compliant contract for construction works'. A Shari'ah compliant contract refers to a contract that incorporates the Islamic belief, practice and value system in its subject matter, agreement, terms and the conditions. The paper is presented in four parts. Part one describes the Shari'ah and its application in business transactions. Part two examines current contract practice for construction works focusing on the primary contract between the Client and the Main Contractor and discusses how such a contract could be presented so that it complies with the Shari'ah. Part three reports an ongoing study focusing on key principles in current contract practice for construction works to ascertain their compliance or otherwise with the Shari'ah. Finally, part four provides a summary and conclusion to the paper. Shari'ah compliant contract offers a new paradigm for contracts for construction works.